Optimization Of Furnace Efficiency In High Vacuum Units: Analyzing Heat Absorption And Loss Methods For Enhanced Fuel Utilization - Nugroho, Budi Sulistiyo; Misqi, Al (Indonesian Scientific Publication, 2024)
One of the operating units of PT. Y, which functions to separate fractions based on differences in boiling routes. Serves to separate fractions based on differences in boiling routes and under vacuum pressure conditions in the High Vacuum Unit (HVU). This is because the feed in this operation contains long residues that consist of long hydrocarbon chain components or have a high boiling point. One of the leading equipment used in this unit is a furnace. The efficiency of furnaces in the High Vacuum Unit (HVU) is critical because furnace efficiency is paramount as it directly influences operational costs and energy consumption in the separation process. The study addresses the problem of optimizing furnace efficiency, which is crucial for reducing fuel usage, particularly fuel gas, thereby enhancing the overall economic viability of the operation. The research employs a methodology that analyzes heat absorbed and heat loss within the furnace system. By measuring these parameters, the study identifies areas for improvement in thermal efficiency. Optimization involves adjusting fuel inputs and operational settings to minimize waste while maintaining effective heating capabilities. The optimization results show a significant decrease in fuel gas usage by 2,14%, compared to the average consumption level recorded in July 2024. In addition, fuel oil usage was optimized to 3 tons per day (T/D). These adjustments improved the furnace's efficiency and contributed to a more sustainable operation. The findings of this optimization study have broader implications for energy efficiency and cost savings in operations. By improving furnace performance, PT. Y can achieve lower operational costs and reduce its environmental footprint through decreased fuel consumption. This aligns with the industry trend towards sustainability and efficient resource management, benefiting the company and society.